PENGEMBANGAN OBJEK WAKAF DALAM FIQIH ISLAM DAN HUKUM POSITIF DI INDONESIA (UIN Sunan Kudus, 2017)
In jurisprudence there is an idea of waqf mu’aqqat (waqf only in a certain duration). Imam Malik argues that the waqf contract is Mulazamat (the possession of a waqf object passes from wakif belongs to God-general). However, he argues that waqf is not necessarily done by Mu’abbad (forever); it may be done within a certain period of time, provided that the waqf shall not be withdrawn until the agreed duration is completed. Indonesian Muslims for hundreds of years have already identified waqf with (in the form of) land, and movable objects of a long lasting nature. Thus, Law no. 41 of 2004 and PP No. 42/2006 is projected as a means of social engineering (social engineering), make changes in thoughts, attitudes and behavior of Muslims to breathe with the spirit of the Act. One of the new regulations in the Waqf Act is the development of waqf objects.